Arguments for Phrasal Verbs in Croatian and Their Influence on Semantic Relations in Croatian WordNet - Katunar, Daniela (Array, 2012)
In this paper we introduce the category of phrasal verbs in Croatian lexicon and grammar description in order to show their influence on semantic relations, namely synonymy and polysemy in Croatian WordNet (henceforth CroWN). We discuss the practical and theoretical implications that arise from the introduction of the category of phrasal verbs in the description of the Croatian lexicon. We also address the interaction of synonymy and polysemy as manifested in the semantic relations of phrasal verbs to their monolexemic counterparts and facilitated by the structure of CroWN. The lemmatization of phrasal verbs in Croatian dictionaries and its modification for purposes of improving semantical relations in CroWN is also discussed. We also propose building of the Croatian phrasal verbs database, describe its structure and its further expanison which would facilitate extraction and incorporation of phrasal verbs into CroWN, and thus improve MT systems and information extraction via this computational lexical resource.